Pemanfaatan Digital Marketing Bagi Destinasi Wisata Di Era New Normal - Hariana Restu Fadillah Rahmah; Siti Nur’Aini; Wilma Septia; Putriana Ramaida; Diah Novarida; Septiyani Aziz; Betty Febryanti (Student Scientific Creativity Journal, 2023)
The beginning of 2020 was a nightmare for Indonesia, the Covid-19 pandemic that hit had an extraordinary impact. Tourism, which is the main sector in the process of national development, is not spared from the impacts it presents. This pandemic has hit the tourism industry so that tens of thousands of workers have lost their jobs within 1 month. As time goes by, Indonesia does not continue to fall into misery. The new normal order has made the tourism sector carry out various kinds of innovations to get back up from the downturn caused by the pandemic. One of the innovations made is by maximizing digital marketing for tourist destinations. This study uses a literature study research method using various written sources such as articles, journals, and documents that are relevant to the study in this study. The results of the study show that the use of digital marketing in the tourism sector has several advantages, namely (1) Spending less money and targeting a wider market, (2) Retaining customers by establishing communication in a smooth way, (3) Easy to choose specific targets (4) Its effectiveness is easy to measure. Digital marketing for tourist destinations can utilize and use various online platforms such as websites, social media, mobile applications, and online advertising.